Mortality Risk in COVID-19 Patients with HIV-Comorbidity: Meta-Analysis - Nindita Arum Veibiani; Bhisma Murti; Argyo Demartoto (Masters Program in Public Health, 2022)
Background: Coronavirus disease 2019 or known as COVID-19 is a disease caused by severe acute respiratory coronavirus 2 (SARS-CoV-2). Comorbidities that are risk factors for COVID-19 death include hypertension, diabetes, heart disease, COPD, HIV (Human Immunodeficiency Virus), kidney failure, and cancer. This study aims to estimate the magnitude of the risk of death in COVID-19 patients with comorbid HIV, with a meta-analysis of the primary studies conducted by the previous authors.Subjects and Method: This study is a systematic review and meta-analysis with the following PICO, population: COVID-19 patients. Intervention: HIV comorbidity. Comparison: without co-morbid HIV. Outcome: Mortality. The articles used in this study were obtained from four databases, namely PubMed, Google Scholar, Springerlink, and Science direct, using the search keys